Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Disiplin Kerja Karyawan : Studi Kasus pada PT. Anugrah Adi Jaya Tasikmalaya - Fitri Nuraeni; Rita Tri Yusnita; Arga Sutrisna (CV. Ulil Albab Corp, 2022)
This research was conducted with the aim of knowing the influence of leadership style and motivation on employee work discipline (a study on the Anugrah Adi Jaya Tasikmalaya Company). The method used in this research is a survey method with a quantitative approach. Data collection techniques were obtained directly through questionnaires which were distributed to 47 respondents who were employees of Anugrah Adi Jaya Tasikmalaya Company. The data analysis tool used in this research is path analysis. based on the results of the study, it can be seen that: (1) Leadership style has a positive and significant influence on motivation at Anugrah Adi Jaya company; (2) Leadership style directly has a positive but not significant influence on Work Discipline at Anugrah Adi Jaya company; (3) Motivation directly has a positive but not significant influence on Work Discipline at Anugrah Adi Jaya company; (4) There is influence an no significant Leadership Style on work Discipline through Motivation at Anugrah Adi Jaya company.